Locally injection of cell sheet fragments enhances new bone formation in mandibular distraction osteogenesis: A rabbit model. Issue 7 (12th March 2013) - Ma, Dongyang; Ren, Liling; Yao, Hong; Tian, Wenyan; Chen, Fulin; Zhang, Junrui; Liu, Yanpu; Mao, Tianqiu
ABSTRACT Effective methods to shorten the treatment period of distraction osteogenesis (DO) are needed. To investigate whether injections of osteogenic bone marrow stromal cell (BMSC) sheet fragments could be used to facilitate new bone formation during DO, 30 rabbits underwent bilateral mandibular osteotomy and their mandibles were lengthened at a rate of 0.75 mm/12 h for 6 days after a 5‐day latency period. There were three treatment groups (n = 10 for each group): Serum‐free medium, dissociated BMSCs, and BMSC sheet fragments. A local injection was conducted with a needle directly into the distracted areas immediately after distraction. Rabbits were sacrificed for examination at 3 and 6 weeks after injection. Gross examination, radiographic evaluation, and micro‐CT scanning indicated a significant increase in bony union in the BMSC sheet fragment group, compared with the medium group and the dissociated cell group. The histomorphometric analysis showed more intensive bone formation in the sheet fragment group than the other two groups at each time point. Additionally, the peak load was significantly higher in the fragment group than those in the others. The results show that injection of BMSC sheet fragments promotes bone formation in DO and indicate a promising approach to shorten the treatment period of osteodistraction. © 2013 Orthopaedic Research Society Published by Wiley Periodicals, Inc. J Orthop Res 31:1082–1088, 2013